Street-level methane emissions of Bucharest, Romania and the dominance of urban wastewater. (January 2022) - Fernandez, J.M.; Maazallahi, H.; France, J.L.; Menoud, M.; Corbu, M.; Ardelean, M.; Calcan, A.; Townsend-Small, A.; van der Veen, C.; Fisher, R.E.; Lowry, D.; Nisbet, E.G.; et al.
Abstract: Atmospheric methane (CH4 ) continues to increase, but there are multiple anthropogenic source categories that can be targeted for cost-effective emissions reduction. Cities emit CH4 to the atmosphere from a mixture of anthropogenic CH4 sources, which include, but are not limited to, fugitive emissions from natural gas distribution systems, wastewater treatment facilities, waste-and rainwater networks, and landfills. Therefore, to target mitigation measures, it is important to locate and quantify local urban emissions to prioritize mitigation opportunities in large cities. Using mobile measurement techniques, we located street-level CH4 leak indications, measured flux rates, and determined potential source origins (using carbon and hydrogen stable isotopic composition along with ethane: CH4 ratios) of CH4 in Bucharest, Romania. We found 969 confirmed CH4 leak indication locations, where the maximum mole fraction elevation (above background) was 38.3 ppm (mean = 0.9 ppm ± 0.1 ppm s.e.; n = 2482). Individual leak indicator fluxes, derived using a previously established empirical relation, ranged up to around 15 metric tons CH4 yr -1 (mean = 0.8 metric tons yr -1 ± 0.05, s.e.; n = 969). The total estimated city emission rate is 1832 tons CH4 yr -1 (min = 1577 t yr -1 and max = 2113 t yr -1 ). More than half (58%–63%) of the CH4 elevations were attributed to biogenic wastewater, mostly from venting storm grates and manholes connecting to sewer pipelines. Hydrogen isotopic composition of CH4 and ethane:methane ratios were the most useful tracers of CH4 sources, due to similarities in carbon isotope ratios between wastewater gas and natural gas. The annual city-wide CH4 emission estimate of Bucharest exceeded emissions of Hamburg, Germany by 76% and Paris, France by 90%. Highlights: Scaled city-wide emission estimated for Bucharest is ∼1832 tons CH4 yr -1 . Emissions account for 32%–42% natural gas, 58%–63% wastewater, and 5% from pyrogenic sources. δ 2 HCH4 signatures and C2 H6 :CH4 were more effective for source apportionment compared to δ 13 CCH4 . Calculated emission factor was 1.6 L min -1 km -1, and the leak density was 0.7 leak indicators per km driven.